To be a professor: Academic mobility and publishing performance - Martin Macháček; Aleš Melecký (PLoS ONE, 2025)
Many aspiring academics target a professorship, but only some succeed. This study examines academic market concentration and its consequences in a post-communist country. We analyzed the field of economic sciences over a 22-year period, combining official data on the appointment process with manually collected data on applicants’ publishing performance in the Czech Republic. Using correlation and linear regression analyses, we investigated whether the mobility of candidates for full professorships is related to their research productivity and research visibility. Our findings revealed low migration flows among both domestic and international institutions. This resulted in high rates of inbreeding and potentially negative consequences, including a greater focus on local journals and lower publication performance after appointment. On average, internal candidates produce more publications, but fewer of them are written in a foreign language. This renders them virtually non-existent to the international research community. After becoming professors, internal candidates are also more likely to reduce their publication performance. Implementing a national, performance-based research funding system has yielded favorable results, such as increased publication performance among candidates over time. These effects were significantly higher in the capital, driven by the top Czech university (Charles University). Despite significant policy reforms, Czech higher education still suffers from considerable path dependence. Government bodies should promote competition among higher education institutions through regulation and financing. We discuss several measures that would modify the existing competence promotion model and support the international competitiveness of the higher education sector.